STEAM TEXNOLOGIYASÍN ENGIZIW ARQALÍ ULÍWMA KÁSIPLIK HÁM QÁNIGELIK PÁNLERDIŃ INTEGRACIYASÍNDA KÁSIPLIK KOMPETENTLIKTI JETILISTIRIW - Orınbetov, N. (SCIENCE and SOCIETY, 2023)
In order to improve the content and methods of technological training, taking into account the developed educational regulations for technological training and modern educational technologies and resources, the use of distance learning technologies and the analysis of information on the development of science, the provision of additional professional information. The individualization of educational processes based on digital technologies and the development of distance learning services are considered.